Caryce kryminału. Kryminał kobiecy w Rosji - Stadnik, Małgorzata (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is an attempt to illustrate the female writers influence on the evolution of the crime fiction genre in Russia. It outlines a brief history of the genre, its complexity and the evolution of the main character. The article focuses on the works of the most famous Russian female writers in terms of their contributions to the crime fiction genre. The author also brings attention to the intercultural dialogue which as a result of Chmilewska's direct influence can be found in the novels by the tsarinas of crime fiction.